The effects of mitochondrial Ca2+ transport on intracellular Ca2+ waves in cardiomyocytes - Zhao, Zhenghang; Xiao, Dandan; Fefelova, Nadezhda; Xie, Lai-Hua (Journal of translational medicine, 2012)
Doc number: A67